Overexpression of the CD155 gene in human colorectal carcinoma. Issue 2 (1st August 2001) - Masson, D; Jarry, A; Baury, B; Blanchardie, P; Laboisse, C; Lustenberger, P; Denis, M G
Abstract : BACKGROUND AND AIMS: The Tage4 gene (tumour associated glycoprotein E4) is overexpressed in rat colon tumours and Min mouse intestinal adenomas. The rat Tage4 protein has approximately 40% identity with human CD155, a member of the immunoglobulin superfamily coding for a transmembrane protein capable of serving as an entry receptor for poliovirus, porcine pseudorabies virus, and bovine herpesvirus 1. Analysis of the rat Tage4 gene has revealed structural and functional similarities with the human CD155 gene. We therefore investigated expression of the CD155 gene in human colorectal carcinomas. METHODS: Overall CD155 expression was assessed by semiquantitative reverse transcription-polymerase chain reaction (RT-PCR) and immunohistochemical analysis using tissue specimens from patients with colorectal adenomas and adenocarcinomas. We also used a qualitative RT-PCR assay to determine relative expression of different splicing variants in each sample. RESULTS: mRNA levels of CD155 were increased in six of six colorectal cancer tissues compared with the tumour free colon mucosa. Immunohistochemical analysis revealed an increased level of CD155 protein in 12 of 12 samples. The qualitative RT-PCR assay revealed that relative expression of the different CD155 variant transcripts was similar in the different normal and cancer samples tested, indicating that this overexpression is not associated with a particular mRNA variant generated by alternative splicing of the CD155 gene. CONCLUSION: We have shown for the first time that the CD155 gene is overexpressed in colorectal carcinoma and that this overexpression begins at an early stage in tumorigenesis and continues to late stages.